1999
DOI: 10.1089/152581699319939
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Human Breast Cancer Cells from Hematopoietic CD34+Stem Cells by Dielectrophoretic Field-Flow-Fractionation

Abstract: Dielectrophoretic field-flow-fractionation (DEP-FFF) was used to purge human breast cancer MDA-435 cells from hematopoietic CD34+ stem cells. An array of interdigitated microelectrodes lining the bottom surface of a thin chamber was used to generate dielectrophoretic forces that levitated the cell mixture in a fluid flow profile. CD34+ stem cells were levitated higher, were carried faster by the fluid flow, and exited the separation chamber earlier than the cancer cells. Using on-line flow cytometry, efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 35 publications
4
88
0
Order By: Relevance
“…This trend suggests that the DEP response of the cells was stronger at higher frequencies, as confirmed in the proportionate DEP response data shown in Figure 3 The curve fits for ℜ(f̃C M ) in Figure 3(b) were calculated by modeling the LNCaP cell as a single-shelled dielectric sphere with a frequency-dependent DEP response primarily dictated by a specific membrane capacitance, C membrane [52]. In the high-conductivity cases, the pDEP response and crossover frequency regions were fit well; the magnitude and frequency dependence, as well as the fit value for C membrane , were similar to those previously reported for other cancer cells [54][55][56]. Yang et al reported on DEP separation of LNCaPs from colorectal cancer cells, but used a higher conductivity media (σ m = 300 mS/m) at which LNCaPs experienced nDEP even in the MHz range [44].…”
Section: Dep Characterization Of Lncapssupporting
confidence: 71%
See 1 more Smart Citation
“…This trend suggests that the DEP response of the cells was stronger at higher frequencies, as confirmed in the proportionate DEP response data shown in Figure 3 The curve fits for ℜ(f̃C M ) in Figure 3(b) were calculated by modeling the LNCaP cell as a single-shelled dielectric sphere with a frequency-dependent DEP response primarily dictated by a specific membrane capacitance, C membrane [52]. In the high-conductivity cases, the pDEP response and crossover frequency regions were fit well; the magnitude and frequency dependence, as well as the fit value for C membrane , were similar to those previously reported for other cancer cells [54][55][56]. Yang et al reported on DEP separation of LNCaPs from colorectal cancer cells, but used a higher conductivity media (σ m = 300 mS/m) at which LNCaPs experienced nDEP even in the MHz range [44].…”
Section: Dep Characterization Of Lncapssupporting
confidence: 71%
“…We found that for the applied electric fields that were tested (10 kHz to 10 MHz, up to 10 V pp ), the cells exhibited no measurable pDEP response in both sugar solutions and PBS with σ m > 100 mS/m. Therefore, we minimally diluted both buffer solutions to 70 mS/m, which is two to seven times higher than conductivities used in the majority of DEP cancer cell capture studies [33,[53][54][55]. We obtained similar DEP characterization data for the highconductivity sugar solution and diluted PBS solution, which suggests that diluted PBS is an appropriate substitute for the isotonic sugar solution.…”
Section: Dep Characterization Of Lncapsmentioning
confidence: 75%
“…T he electrical properties of biological cells are of great interest, as they can provide opportunities to develop novel, rapid assays for disease (1,2) and integrated hybrid chips for electronics (3)(4)(5)(6)(7). Previous electrical studies of cells have focused on external macroscopic properties, such as cell membrane responses or volume, and have reflected primarily those of large ensembles of cells (8,9).…”
mentioning
confidence: 99%
“…84) have firmly demonstrated that human cell populations of different histotype and differentiation stage are able to be isolated using DEP-based devices. These features propose Lab-on-a-chip platforms for diagnostic applications, cell separation and characterization in the field of non-invasive prenatal diagnosis (88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98).…”
Section: Dep-based Lab-on-a-chip Devices With High-density Arrayed Elmentioning
confidence: 99%